2021
DOI: 10.3389/fgene.2021.759129
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Multiple Exostoses—A Review of the Molecular Background, Diagnostics, and Potential Therapeutic Strategies

Abstract: Hereditary multiple exostoses (HMEs) syndrome, also known as multiple osteochondromas, represents a rare and severe human skeletal disorder. The disease is characterized by multiple benign cartilage-capped bony outgrowths, termed exostoses or osteochondromas, that locate most commonly in the juxta-epiphyseal portions of long bones. Affected individuals usually complain of persistent pain caused by the pressure on neighboring tissues, disturbance of blood circulation, or rarely by spinal cord compression. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 78 publications
0
25
0
1
Order By: Relevance
“…Mutations in either the EXT1 or EXT2 gene in humans are associated with hereditary multiple exostoses, a skeletal disorder characterized by formation of osteochondromas 37 . We compiled a list of all known single amino acid patient mutations linked to a loss-of-function of EXT1 and EXT2 and mapped them onto the complex structure.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in either the EXT1 or EXT2 gene in humans are associated with hereditary multiple exostoses, a skeletal disorder characterized by formation of osteochondromas 37 . We compiled a list of all known single amino acid patient mutations linked to a loss-of-function of EXT1 and EXT2 and mapped them onto the complex structure.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Inubushi et al ( 16 ) reported a connection between increased BMP signaling and osteochondromagenesis, which serves an essential role in skeletal development by regulating chondrocyte proliferation and differentiation; they also suggest that treatment with a BMP inhibitor may be effective in patients with HME, which showed promising results in their study conducted on mouse models. Bukowska-Olech et al ( 12 ) hypothesized that heparanase, an enzyme that cleaves the heparan sulfate (HS) chains and stimulates chondrogenesis, is physiologically found only in the hypertrophic zone and perichondrium, and its wider distribution and increased activity possibly served a role in the development of osteochondromas.…”
Section: Introductionmentioning
confidence: 99%
“…Although several risk factors and pathogenic mechanisms have been hypothesized, it is most frequently suggested that mutations in exostosin glycosyltransferase 1 (EXT-1) and EXT-2 , genes with autosomal dominant inheritance, are the most likely responsible factors for HME ( 2 , 12 ), having been detected in 28–65% and in 21–61% of the affected patients, respectively ( 1 ). EXT-1 is located on chromosome 8q24,11-q24.13 and EXT-2 on chromosome 11p11-12 ( 11 ); both encode glycosyltransferases and serve vital roles in the synthesis of HS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in either the ext1 or ext2 gene in humans are associated with hereditary multiple exostoses, a skeletal disorder characterized by formation of osteochondromas 36 . We compiled a list of all known single amino acid patient mutations linked to a loss-of-function of EXT1 and EXT2 and mapped them onto the complex structure.…”
Section: Introductionmentioning
confidence: 99%